INTEGRAÇÃO DE BASE DE USUÁRIOS UTILIZANDO LDAP - Priedols, Anderson A. M.; Boniati, Bruno B.; Geib, Heini T.; Fridhein, Maiquel J. F.; Ávila, Andre d.; Buske, Dionei F.; Jr., Ivo C.; Jr., Júlio C. B.; Müller, Liris (Salão do Conhecimento, 2013)
Resumo